Pendidikan Kesehatan Tentang Diabetes Mellitus - Sawitri, Endang; Kusumaningrum, Puput Risti; Rusminingsih, Esri; Kusumawati , Ema (WASATHON Jurnal Pengabdian Masyarakat, 2025)
Diabetes Mellitus (DM) is a chronic disease with a globally increasing prevalence, including in Indonesia. This condition is characterized by high blood sugar levels due to impaired insulin production or function, which can lead to serious complications. A health education session on Diabetes Mellitus was conducted, to enhance community awareness regarding risk factors, symptoms, prevention, and DM management. The method included preparation, direct delivery of materials, and interactive evaluation. Results showed an increase in community understanding of DM, including its definition, symptoms, risk factors, and preventive measures. Participants also demonstrated greater awareness of adopting healthy lifestyles and improving DM management. This education program is expected to reduce the risk of complications and improve the community’s quality of life.